Ferromagnetic Microwire Composites From Sensors to Microwave Applications - Peng, Hua-Xin; Qin, Faxiang; Phan, Manh-Huong (Engineering Materials and Processes,, 2016)
Situated at the forefront of interdisciplinary research on ferromagnetic microwires and their multifunctional composites, this book starts with a comprehensive treatment of the processing, structure, properties and applications of magnetic microwires. Special emphasis is placed on the giant magnetoimpedance (GMI) effect, which forms the basis for developing high-performance magnetic sensors. After defining the key criteria for selecting microwires for various types of GMI sensors, the book illustrates how ferromagnetic microwires are employed as functional fillers to create a new class of composite materials with multiple functionalities for sensing and microwave applications. Readers are introduced to state-of-the-art fabrication methods, microwave tunable properties, microwave absorption and shielding behaviours, as well as the metamaterial characteristics of these newly developed ferromagnetic microwire composites. Lastly, potential engineering applications are proposed so as tohighlight the most promising perspectives, current challenges and possible solutions. .